ISLAMOPHOBIA IN INDIA: AN EXPLORATION OF ITS ROOTS, RISE AND HISTORY - Ushama, Thameem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
As a product of Hindu Fascists, Islamophobia in India is reviewed from the beginning of the twentieth century through to India’s 2019 Parliamentary elections. A qualitative content analysis clearly shows that Hindutva proponents disseminated the ideology with a view to establish Hindu Rashtra to the exclusion of Muslims. The paper focuses on documented actions taken by individuals, political leaders, parties and various Hindu organisations to cultivate hatred for Muslims by endorsing communal violence, mosque and communal destruction, genocidal murders, and various political movements designed to remove Muslims from India.